Six billion and beyond - Linda Harrar Productions (Berkeley, CA : Berkeley Media LLC, 1999)
Explores the issues of population growth and the issues surrounding it: reproductive health, overpopulation, and the environment in six nations: Mexico, Kenya, India, China, Italy, and the United States
Host: Blythe Danner
DVD format
Keywords: Overpopulation; Population; Sustainable development; Birth control; Reproductive health